Experimental investigation of carbon dioxide trapping due to capillary retention in saline aquifers. Issue 4 (30th January 2015) - Li, X.; Akbarabadi, M.; Karpyn, Z. T.; Piri, M.; Bazilevskaya, E.
Abstract: Capillary trapping is a physical mechanism by which carbon dioxide (CO2 ) is naturally immobilized in the pore spaces of aquifer rocks during geologic carbon sequestration operations, and thus a key aspect of estimating geologic storage potential. Here, we studied capillary trapping of supercritical carbon dioxide (scCO2 ), and the effect of initial scCO2 saturation and flow rate on the storage/trapping potential of Berea sandstone. We performed two‐phase, scCO2 ‐brine displacements in two samples, each subject to four sequential drainage–imbibition core‐flooding cycles to quantify end‐point saturations of scCO2 with the aid of micro‐ and macro‐computed tomography imaging. From these experiments, we found that between 51% and 75% of the initial CO2 injected can be left behind after the brine injection. We also observed that the initial scCO2 saturation influenced the residual scCO2 saturation to a greater extent than the rate of brine injection under the experimental conditions examined. In spite of differences in the experimental conditions tested, as well as those reported in the literature, initial and residual saturations were found to follow a consistent relationship. Abstract : Retention of CO2 by capillary trapping in sandstone samples can reach about 38% of residual CO2 saturation according to empirical model fitting to the experimental data presented in this work. In spite of relative differences in permeability and experimental conditions tested in this study, and those reported in the literature, initial and residual saturations follow a consistent relationship. Empirical modeling of this relationship proved to be sound and of practical use in estimating capillary trapping in sandstones.